Mathematical Definition of Cutting Ability of Knives - Urinov Nasillo Fayzilloevich; Sayliev Ismat Ismatovich; Odinaev Rustam Sobirovich (Research Parks Publishers, 2021)
The article covers an analytical expression for calculating the cutting ability of thin lamellar knives, considering the characteristics of longitudinal and transverse microrelief of blade and cutting modes. The main parameters of microgeometry that determine the cutting ability of blades are the width of the cutting edge, the height and longitudinal pitch of the micro-teeth, and the characteristics of the reference curve.